Evaluation of occupational health literacy of health workers in Adana, Türkiye - Dağlı, Fatma İrem and İnaltekin, Ayşe and Sadıkoğlu, Hatice Merve and Makca, Tuba and Tanır, Ferdi and Demirhindi, Hakan (Scientific Reports in Medicine, 2024)
Objective: The importance of occupational health and safety (OHS) and related health literacy is increasing. The aim of this study was to evaluate the occupational health literacy status of healthcare workers in Adana (Turkey). Method: The population of the study consists of health workers in Adana province (N=18,660). Between April 29 and June 13, four researchers visited the workplaces of health workers and asked them to answer online survey questions through the WhatsApp application in face-to-face meetings. The study was completed with 179 individuals determined using non-probability sampling method. The analyses were performed using the SPSS 22 software. The Kolmogorov-Smirnov, t-test, Mann-Whitney U test, ANOVA, and Kruskal-Wallis test were used in the analyses. A significance level of p < 0.05 was considered statistically significant. Results: The study included 179 healthcare workers with an average age of 32.36±7.97 years. Pre-employment medical examinations and periodic examinations were reported to have been performed in 65.9% and 50.3%, respectively. The "Occupational Health Literacy Scale" that was administered to the participants with a resulting avarage score was 80.30±11.68. Participants who underwent workplace periodic examinations had higher scores in Factor 1 and Factor 4 compared to those who did not undergo any periodic examination. Conclusion: Participants who underwent periodic examinations and those who were informed about health risks had higher occupational health literacy. It is recommended that health workers be informed about health risks in the institutions they work, periodic examinations are carried out regularly, OHS trainings are planned, and these trainings are repeated periodically.